ANALISIS PENGARUH MEDIA SOSIAL DAN BUDAYA POP TERHADAP PERILAKU MURID KELAS V SERTA UPAYA PENGUATAN LITERASI MEDIA - Intan Junaeda; Suardi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the influence of social media and popular culture on the behavior of fifth-grade students and explores strategies for strengthening media literacy at SDN 24 Batangase. In the digital era, elementary school students are increasingly exposed to various social media platforms and popular culture trends that shape their communication patterns, learning motivation, and social behavior. The objectives of this research were to analyze the level of social media use among students, identify its positive and negative impacts on student behavior, determine factors contributing to low media literacy, and formulate recommendations for media literacy reinforcement in schools. This study employed a qualitative descriptive approach supported by quantitative data, using observations, semi-structured interviews, questionnaires, and document analysis as data collection techniques. The research subjects consisted of fifth-grade students, classroom teachers, and parents. The findings indicate that social media and popular culture significantly influence students’ language use, learning concentration, social interaction, and self-confidence. While some students benefit from educational digital content, many experience decreased focus and tend to imitate viral trends without critical evaluation. The results also reveal that students’ media literacy skills are still limited, particularly in evaluating content credibility, digital ethics, and online safety. Therefore, strengthening media literacy through collaborative efforts involving schools, teachers, and parents is essential. Integrating media literacy into learning activities, utilizing popular culture positively, and providing continuous guidance are recommended to help students develop critical, responsible, and character-based digital behavior.